2016
DOI: 10.1111/1468-5973.12111
|View full text |Cite
|
Sign up to set email alerts
|

What Business Owners Expect From a Crisis Manager? A Competency Model: Survey Results From Czech Businesses

Abstract: This competency model of a crisis manager has been developed based on cooperation with managers and experts in the field of crisis management. The brainwriting method was used to generate an overview of the competencies expected of a crisis manager. Using a mind map three basic groups of competencies were developed. The participants used Saaty's method to determine the significance of individual competencies. The different attributes of individual competencies according to the level of their development were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…Successful and effective managers are selected based on merit and have unique characteristics, including behaviors, skills, knowledge, attitudes, and personality traits (23). The current study's findings are in agreement with the results of other studies (24)(25)(26)(27). The competencies required for success are combined to create the competence model in the modeling process.…”
Section: Discussionsupporting
confidence: 93%
“…Successful and effective managers are selected based on merit and have unique characteristics, including behaviors, skills, knowledge, attitudes, and personality traits (23). The current study's findings are in agreement with the results of other studies (24)(25)(26)(27). The competencies required for success are combined to create the competence model in the modeling process.…”
Section: Discussionsupporting
confidence: 93%
“…Integrity is number 5 on the list and the second crisis competency is not consistent with those identified by Mikušová and Čopíková (2016). The respondents indicated that integrity together morals and ethics play a big part when leading during a crisis.…”
Section: The Findings and Discussionmentioning
confidence: 85%
“…(Mikušová & Čopíková, 2016) Herbane (2010) states, 'a person feels the threat of a crisis, they will react intuitively and deal with the crisis at hand'. Mikušová and Čopíková (2016) identified several critical competencies needed within the field of crisis management from the business owner's point of view. In their study, Mikusiva and Copikova state that crisis managers use a variety of competencies which are clustered into three categories.…”
Section: Crisis Management Competenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Saaty's method was selected for multicriteria evaluation. Its suitability was proved by the studies of Borovcová and Špačková (2018), Peterková & Franek (2018) or Mikušová & Čopíková, (2016). It is obvious that, apart from the accuracy criterion, the other criteria will be strongly interconnected with the company's size.…”
Section: Methodological Approachmentioning
confidence: 99%